The Influences of Financial Development, Economic Growth, Energy Price, and Foreign Direct Investment on Renewable Energy Consumption in The BRICS - Islam, Samanta; Raihan, Asif; Ridwan, Mohammad; Rahman, Md. Shoaibur; Paul, Arindrajit; Karmakar, Sourav; Paul, Pramila; Tanchangya, Tipon; Rahman, Junaid; Jubayed, Abdullah Al (Journal of Environmental and Energy Economics, 2023)
This study seeks to look into the effects of financial development, economic growth, consumer price index (CPI), and foreign direct investment (FDI) on renewable energy utilization. The investigation applied the panel dynamic ordinary least squares (DOLS) methodology by using yearly time-series data from 1990 to 2022 for the BRICS nations (Brazil, Russia, India, China, and South Africa). The empirical results show an upward trend involving financial development and the use of renewable energy, suggesting that financial development precedes the uptake of renewable energy. In a similar vein, there are noteworthy positive associations found between the CPI and economic growth when renewable energy is used. Furthermore, a surprising link between direct investment and the use of renewable energy is also revealed by our research. These findings offer insightful information about the factors influencing the use of renewable energy in the BRICS nations. From a policy standpoint, the results support the implementation of policies that encourage the uptake of clean technology in conjunction with strong efforts to promote the adoption and exploitation of renewable energy sources. Such actions can promote economic expansion and help the BRICS economies meet their sustainability and low-carbon commitments. The adoption of renewable energy in the examined bloc can be made even more cost-effective by taking practical measures, such as feed-in tariffs and subsidies. By providing evidence-based insights, this study advances the worldwide fight against climate change and the quest for affordable and sustainable energy.